Recovery of heavy metals from spent etching waste solution of printed circuit board (PCB) manufacturing - M. Ali, A. H.; Sobri, Shafreeza; Ali, Salmiaton; Md. Yasin, Faizah (Universiti Putra Malaysia Press, 2013)
The process of etching is the most crucial part of the work of manufacturing printed circuit boards (PCB). In the etching process by nitric acid, a spent etching waste solution of composition 250 g/L HNO3, 30-40 g/L Cu, 30-40 g/L Sn, 30-40 g/L Pb and 20-25 g/L Fe is produced. High metal concentrations in the spent etching waste solution make it a viable candidate for the recovery of metals. Recovery of metals from spent etching waste solution is a significant concern as the recent growth in production of printed circuit boards has generated a drastic increase of spent etching waste solution each year. This study concerns itself with the recovery of metals from spent etching waste. In this study a dilution was made in order to increase the pH of the solution as spent etching waste solution has high acidity, and the electrowinning method was performed to recover metals from the spent etching waste solution. Glassy carbon and platinum were used as cathode and anode in order to investigate the electrodeposition of metals and cyclic voltammetry investigation suggests that the deposition of metals on glassy carbon electrodes occurs at four different overpotentials mainly at -0.15 V, -0.35 V, -0.45 V and -0.75 V. Microscopy observation demonstrates that there is a deposition of metals by applying the potentials in a set of current-time transient study for a duration of 60 seconds and the metals recovered formed as aggregates.